Boundary element modelling of a piezoelectric transformer - Mahirah Mazlan (2016)
Analysing the anti-plane harmonic vibration of a ceramic slab by a boundary integral method. This ceramic slab is being subjected to an electrical load. Moreover, such problem is usually considered in applications such as the analysis of piezoelectric transformers. For this case, this ceramic slab would be acting as the piezoelectric transformer. Thus, there are important quantities that can be achieved through computation. Such quantities that are being considered would be the transforming ratio and the efficiency of the ceramic slab. Analysing the differences of the transforming ratio and efficiency where the electrodes are being placed at different points of the ceramic slab. The elements are being considered at all points of the ceramic slab. This will include the comparison of the graphs with another ceramic slab of difference in height. The pattern of the graphs for each ceramic slab is to be analyse and being compared with the true graphs as accordance to the reference of the analysis of a rectangular ceramic plate in electrically forced thickness-twist vibration as a piezoelectric transformer.